Intragroup and Intergroup Pairwise Key Predistribution for Wireless Sensor Networks - Ching-Nung Yang; Ting-Song Gu; Jhou-Cian You; Chang-Ji Wang (Sensors)
The major task of a wireless sensor network (WSN) is data collection. Key predistribution (KP) is to establish pairwise keys for secure communication in a WSN, such that all collected data could be securely sent to a backend database. Most research on KP-like schemes is dedicated to enhancing resiliency against node capture attack (NA) and retaining the link connectivity in the meantime. For large-scale wireless sensor networks, a more common approach is to use a multiple-sink WSN (MWSN) to support a large number of sensor nodes. In MWSNs, there are different clusters (referred to as groups). We took the lead in studying KP in the MWSN environment. Based on the new MWSN environment, we present intragroup and intergroup KP (I2KP) to fulfill both requirements of security and energy efficiency when gathering data via various sink nodes in a large-scale WSN. Three types of I2KP with respective pros and cons are proposed. Theoretical analysis and numerical simulation demonstrate their effectiveness.